Biomarker characteristics of oils from Garmian Oil Fields and potential Jurassic source rocks, Kurdistan,NE Iraq: implications for oil–oil and oil-source rocks correlation. - Saeed, Diyar A.; Mohialdeen, Ibrahim M.J. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The Middle Jurassic Sargelu Formation in Sangaw North -1 (SwN-1) borehole, Sangaw North Block, Garmian area, Kurdistan region, was used for geochemical analyses. Two crude oils from PLK-8 and Sarqala-1 wells in Pulkhana and Sarqala oil fields, one condensate from KM-3 well in Kor Mor gas field and seepage oil from ChiaSurkh oil field were chosen for organic geochemistry investigation, oil-oil and oil-source rocks correlation. Tectonically, the study area is located in the southeastern part of the Foothill Zone in Zagros Fold Belt. The biomarkers ratios and molecular compound distributions showed that the oils, condensate and rock extracted sample of Sargelu Formation were derived from marine carbonate source rocks bearing marine algae and kerogen type II that deposited under reducing condition. Low presence of gammacerane indicated normal salinity condition during the depositions. The GC-FID traces of oils and condensate showed lack of any remarkable biodegradation, but rock-extracted of Sargelu Formations is strongly contaminated by polyethylene glycol according to the GC-FID chromatogram. Compositional similarity of sterane, hopane, isopernoid and n-alkane compounds among the crude oils and crude oils with extracted sample of Sargelu Formation suggested that the oils might be sourced from the same or similar source rocks that deposited under similar conditions. On the other hand, Sargelu Formation is supposed to be one of the sources of the generated crude oils. However, the maturity-related parameters showed no similarity between the crude oils and extracted sample of Sargelu Formation.
Keywords: KurdistanGarmianSangawSargeluoilsource correlationBiomarkers